2023
DOI: 10.2174/0929867329666220615124412
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacology of Organoselenium Compounds in Mental Disorders and Degenerative Diseases

Abstract: Neurodegenerative and mental disorders are a public health burden with pharmacological treatments of limited efficacy. Organoselenium compounds are receiving great attention in medicinal chemistry mainly because of their antioxidant and immunomodulatory activities, with a multi-target profile that can favor the treatment of multifactorial diseases. Therefore, the purpose of this review is to discuss recent preclinical studies about organoselenium compounds as therapeutic agents for the management of mental (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 229 publications
0
12
0
Order By: Relevance
“…A scanning electron microscope is one of the best microscopes To study the surface quality, where Cross section of the nanostructurejresult appeared the photomicrograph for FESEM on about facilitator, An image was usedSEM to determine the shape and size of the biosynthetic nanoparticles, where they were found in different sizes and using different magnification powers, and the results were examined, as the electronic scanning of SeNPs showed that the basic shape of the particles is a rod and the particles were homogeneous in sizeand figTo some extent ,program was usedImage JTo measure the diameters of nanoparticles were the extentTheir diameters range between nmAs in Figure (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The results of these dimensions show convergence with what has been achieved (Chhabria & Desai, 2016).Where she wasSeNpsincluded in their studiesrodAnd the dimensions of its diameters are 59_+4.…”
Section: Characterization Of Nanoparticles Field Emission Scanning El...mentioning
confidence: 99%
“…A scanning electron microscope is one of the best microscopes To study the surface quality, where Cross section of the nanostructurejresult appeared the photomicrograph for FESEM on about facilitator, An image was usedSEM to determine the shape and size of the biosynthetic nanoparticles, where they were found in different sizes and using different magnification powers, and the results were examined, as the electronic scanning of SeNPs showed that the basic shape of the particles is a rod and the particles were homogeneous in sizeand figTo some extent ,program was usedImage JTo measure the diameters of nanoparticles were the extentTheir diameters range between nmAs in Figure (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The results of these dimensions show convergence with what has been achieved (Chhabria & Desai, 2016).Where she wasSeNpsincluded in their studiesrodAnd the dimensions of its diameters are 59_+4.…”
Section: Characterization Of Nanoparticles Field Emission Scanning El...mentioning
confidence: 99%
“…Moreover, selenomethionine 1 has been considered as a potential candidate for the treatment of coronavirus infections owing to its antioxidant and immunomodulatory properties [ 43 , 44 ]. Lastly, ebselen 4 and its derivatives exhibited neuroprotective effects against different toxicants, thus suggesting a possible future interest in managing mental disorders and degenerative diseases [ 45 , 46 , 47 ].…”
Section: Selenium-containing Compounds As Therapeutic Agentsmentioning
confidence: 99%
“…Due to the biological significance of antioxidants, there have been various attempts to replicate their action using specific types of small molecules, such as selenium (Se) compounds. Ebselen ( 1 ) is the most extensively studied cyclic selenenamide found to be a good GPx mimic and anti-inflammatory agent (Figure ). , …”
Section: Introductionmentioning
confidence: 99%